2007
DOI: 10.1021/es062122i
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pathogenic Prion Protein to Quartz Sand

Abstract: Management responses to prion diseases of cattle, deer, and elk create a significant need for safe and effective disposal of infected carcasses and other materials. Furthermore, soil may contribute to the horizontal transmission of sheep scrapie and cervid chronic wasting disease by serving as an environmental reservoir for the infectious agent. As an initial step toward understanding prion mobility in porous materials such as soil and landfilled waste, the influence of pH and ionic strength (I) on pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
123
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(131 citation statements)
references
References 35 publications
7
123
1
Order By: Relevance
“…Prions bind strongly to various types of soil and resist removal by water or various solvents (Leita et al, 2006;Saunders et al, 2008) so though possibly long-lasting, there is little subsequent migration or leaching through the soil (Jacobson et al, 2010;Maddison et al, 2010). Prions may interact with various components of soil including clay, sand and organic components (Ma et al, 2007;Maddison et al, 2010;Saunders et al, 2010). In vitro and laboratory assays have indicated that prions bound to clays may have greater infectivity (Johnson et al, 2006) while field studies by Walter et al (2011) showed an association between CWD in mule deer and a higher percentage of clay soils within the deer's home range.…”
Section: Introductionmentioning
confidence: 99%
“…Prions bind strongly to various types of soil and resist removal by water or various solvents (Leita et al, 2006;Saunders et al, 2008) so though possibly long-lasting, there is little subsequent migration or leaching through the soil (Jacobson et al, 2010;Maddison et al, 2010). Prions may interact with various components of soil including clay, sand and organic components (Ma et al, 2007;Maddison et al, 2010;Saunders et al, 2010). In vitro and laboratory assays have indicated that prions bound to clays may have greater infectivity (Johnson et al, 2006) while field studies by Walter et al (2011) showed an association between CWD in mule deer and a higher percentage of clay soils within the deer's home range.…”
Section: Introductionmentioning
confidence: 99%
“…Prions can persist in soils for years (Seidel et al, 2007;Brown & Gajdusek, 1991) and binding of PrP TSE by soil particles may maintain prions near the soil surface, thereby increasing animal exposure (Johnson et al, 2006;Cooke et al, 2007;Ma et al, 2007). Soil particle-associated agents are infectious orally (Seidel et al, 2007;Johnson et al, 2007).…”
mentioning
confidence: 99%
“…Protein attachment to negatively charged surfaces is often maximal at the isoelectric point (pI) of the protein and declines when pH.pI due to repellent electrostatic interactions (Quiquampoix et al, 2002). The apparent average pI of PrP TSE aggregates is~4.6 (Ma et al, 2007); prion protein aggregates carried no net charge around this pH value. In most models of degradation of organic molecules by MnO 2 , sorption to the oxide surface represents a critical initial step (Stone, 1987).…”
mentioning
confidence: 99%
“…[14][15][16]19,[26][27][28] Prions have a strong affinity for clay minerals commonly found in soil; PrP Sc binds clay minerals (montmorillonite, Mte) avidly in comparison with quartz sand, an interaction that considerably enhances prion infectivity.…”
Section: Prion Interactions With Different Soil Compoundsmentioning
confidence: 99%